PENGARUH BRAND AMBASSADOR, BRAND IMAGE DAN KOREAN WAVE TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Pembeli Produk McD BTS Meal di Jakarta Utara) - Hakiki, Intan Nur (JOURNAL OF BUSINESS STUDIES, 2022)
This study aims to determine the effect of Brand ambassador, Brand image and Korean wave on the Purchase Decision of McD BTS meal. McDonald's is the largest fast food restaurant in the world. Quantitative research method, a sample of 100 respondents using purposive sampling McD BTS meal buyers. The research data is primary data collected by distributing questionnaires to respondents who have purchased McD BTS meal. Hypothesis testing was carried out using the Statistical Program for Social Science (SPSS) data analysis method version 25. The results showed that Brand ambassador had a negative and insignificant impact on the Purchase Decision of the McD BTS meal. Brand image has a positive and significant impact on the Purchase Decision of McD BTS meal. Korean wave has a positive and significant impact on the Purchase Decision of McD BTS meal.